Lily's story eaudiobook - Cameron, W. Bruce (A Dog's Purpose Puppy Tales., 2019)
A rescue dog to the rescue! Lily is the smallest puppy in her litter and the only girl. Her brothers are bigger and stronger and like to push her around. When Lily meets a girl named Maggie Rose at the animal shelter, Lily discovers things are not so bad. Lily's size means that she can help other animals who are in trouble. It's Lily to the rescue!